CALVING INTERVAL PADA SAPI BALI DI KABUPATEN PRINGSEWU - Bastian Rusdi; Madi Hartono; Sri Suharyati (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
Research on calving interval in Bali Cattles in Pringsewu Regency was held on December 2014 until January 2015 with 5 inseminators, 110 Bali Cattles that had been inseminated belong to 100 farmers. Purposes of this reserch were to know: 1) value calving interval of Bali Cattles in Pringsewu Regency, 2) the factors and magnitude factors which disturb calving interval of Bali Cattles in Pringsewu Regency. This research used sensus method, data obtained was real data that present and accuread in Pringsewu Regency. Data was analyzed by logistic regression with SPSS (Statistics Packet for Social Science) program. The results showed that calving interval of Bali Cattle at Pringsewu Regency is 416.69 days. Factors that affect the value of calving interval in Bali Cattle in Pringsewu Regency derived from inseminator level factors that affect it are long thawing. Old thawing major factors positively associated with 2,389. In addition, factors that affect the value of calving interval at the farmer level is reason to raise as savings associated negatively with huge factor 33.102, the formal education of farmers, namely SD of 68%, middle 19%, and high schools 13% were positively associated with large factor 8.467, layout cage positively associated with large factor 0.433, floor cage positively associated with large factor 21.705, spacious cages associated negatively with huge factor 0.741, the age of weaning calves were positively associated with a large factor of 0.081, the S/C is positively associated with a large factor 17.665 , marriage is positively associated with postpartum major factor of 0,965, reproductive status associated with major negative factor of 187.890. Keywords: Bali Cattle, Calving Interval, Pringsewu Regency, Value